The Rise of Student Social Movement: Case Study of #GejayanCalling Movement in Yogyakarta - Mahpudin, Mahpudin; Kelihu, Ardiman; Sarmiasih, Mia (HK-Publishing, 2020)
This paper discusses the rise of student social movements in response to the presence of a crisis of public legitimacy triggered by the failure of the government to carry out the functions of the state and failure to realize the welfare of society. The climax when the government and the parliament agreed to revise the rules regarding the authority of the Corruption Eradication Commission (Komisi Pemberantasan Korupsi, KPK) which was considered by many elements of civil society as weakening the KPK. This issue became the dominant discourse and triggered the presence of other issues and demands. The focus of this study is the #GejayanCalling movement initiated by a number of students in Yogyakarta who successfully attracted the sympathy and support of thousands of students and various elements of civil society to take to the streets. This paper uses qualitative research methods with a case study approach. The data collection is done through primary data through interviews with key informants and secondary data through literature studies. The results of the study revealed that the #GejayanCalling movement became massive and significant through the consolidation and political compromise undertaken by students in managing the movement to respond to public unrest marked by a crisis of public legitimacy towards the government. The protest was able to attract thousands of students because of the emphasis on the issue by overriding the role of certain figures, actors or organizations. Emphasis on issues rather than actors becomes an effective strategy in creating shared goals and collective action. Besides that, the use of social media as a repertoire of movements in framing issues is very contributing to strengthen demonstration.Â Penelitian ini membahas kebangkitan gerakan sosial mahasiswa sebagai tanggapan terhadap adanya krisis legitimasi publik yang dipicu oleh kegagalan pemerintah untuk menjalankan fungsi negara dan kegagalan untuk mewujudkan kesejahteraan masyarakat. Puncaknya ketika pemerintah dan parlemen sepakat untuk merevisi aturan mengenai kewenangan Komisi Pemberantasan Korupsi (KPK) yang dianggap oleh banyak elemen masyarakat sipil sebagai pelemahan KPK. Masalah ini menjadi wacana dominan dan memicu kehadiran isu dan tuntutan lainnya. Fokus penelitian ini adalah gerakan #GejayanCalling yang diprakarsai oleh sejumlah siswa di Yogyakarta yang berhasil menarik simpati dan dukungan ribuan siswa dan berbagai elemen masyarakat sipil untuk turun ke jalan. Makalah ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui data primer melalui wawancara dengan informan kunci dan data sekunder melalui studi literatur. Hasil penelitian mengungkapkan bahwa gerakan #GejayanMemanggil menjadi masif dan signifikan melalui konsolidasi dan kompromi politik yang dilakukan oleh siswa dalam mengelola gerakan untuk menanggapi keresahan publik yang ditandai oleh krisis legitimasi publik terhadap pemerintah. Protes ini mampu menarik ribuan siswa karena penekanan pada masalah ini dengan mengesampingkan peran tokoh, aktor atau organisasi tertentu. Penekanan pada masalah daripada aktor menjadi strategi yang efektif dalam menciptakan tujuan bersama dan tindakan kolektif. Selain itu, penggunaan media sosial sebagai repertoar gerakan dalam membingkai isu sangat berkontribusi untuk memperkuat demonstrasi.